Temperature sensitivity of silicon nanowire transistor based on channel length - AlAriqi, Hani Taha; Jabbar, Waheb A.; Hashim, Yasir; Hadi, Manap (IEEE, 2019)
This paper investigates the temperature sensitivity of Silicon Nanowire Transistor (SiNWT) depends on the gate length, and also presents the possibility of using it as a Nano- temperature sensor. The MuGFET simulation tool was used to investigate temperature characteristics of the nanowire. Current-voltage characteristics with different values of temperature and with different length of the Nano wire gate (Lg = 25, 45, 65, 85 and 105 nm), were simulated. MOS diode mode connection suggested to measure the temperature sensitivity of SiNWT. The final results show that the best temperature sensitivity of SiNWT based in largest ΔI occurred at working voltage VDD range 1 V to 3.5 V, depends on channel length range 25 nm to 85 nm and beyond the temperature sensitivity will be constant even the channel length increased up to 105 nm.